Unemployment and labor force participation across the US States: New evidence from panel data - Nicholas Apergis; Ibrahim Arisoy (SPOUDAI - Journal of Economics and Business, 2017)
This study examines the relationship between unemployment and labor force participation to judge the presence of the discouraged worker/added worker/unemployment invariance effect in the US labor market, spanning the period 1976-2014. Panel unit root and cointegration tests explore this relationship. The results indicate the presence of a relationship between unemployment and labor force participation rates, while the impact of unemployment on labor force participation is negative, indicating the prevalence of the discouraged worker effect across the US. These findings receive statistical support through panel causality tests, while they carry significant policy implications in relevance to labor policies across the US states.
Keywords: E24; J60; 330; unemployment invariance hypothesis; discouraged worker effect; labor force participation rates; unemployment rates; US states panel data